Toward Understanding the Simulated Phase Partitioning of Arctic Single‐Layer Mixed‐Phase Clouds in E3SM - Meng Zhang; Shaocheng Xie; Xiaohong Liu; Wuyin Lin; Kai Zhang; Hsi‐Yen Ma; Xue Zheng; Yuying Zhang (Earth and Space Science, 2020)
Abstract Arctic mixed‐phase clouds simulated by the U.S. Department of Energy (DOE) Energy Exascale Earth System Model (E3SM) Atmosphere Model version 1 (EAMv1) are found to be overly dominated by supercooled liquid with little ice production. Sensitivity experiments using the short‐term hindcast approach are performed to isolate the impact of several new parameterizations on the simulated mixed‐phase clouds in EAMv1. These include the Classical Nucleation Theory (CNT) ice nucleation scheme, the Cloud Layer Unified By Binormals (CLUBB) parameterization, and the updated Morrison and Gettelman microphysics scheme (MG2). Results are compared to the DOE's Atmospheric Radiation Measurement (ARM) Mixed‐Phase Arctic Cloud Experiment (M‐PACE) observations. It is found that all of these new parameterizations are responsible for the decrease of cloud ice water content in EAMv1 simulated single‐layer mixed‐phase clouds. A budget analysis of detailed cloud microphysical processes suggests that a lack of initial ice particles from ice nucleation or convective detrainment strongly diminishes the cloud ice water content through the subsequent ice mass growth processes. Reduced heterogeneous ice nucleation by CNT at temperatures warmer than −15°C along with negligible ice processes in CLUBB are primarily responsible for the problem. Because the use of MG2 does not impact initial ice formation, the MG2 cloud microphysics is not the primary reason for the underestimate of cloud ice. However, using MG2 leads to a lower total ice mass due to a higher accretion rate of liquid droplets by rain drops and a lower ice mass growth rate.